DIFFERENCES IN S-RBD ANTIBODY TITERS OF SARS-CoV-2 POST-VACCINATION AND POST-COVID-19 IN UMY EMPLOYEES THAT DO GENERAL MEDICAL CHECK UP AT AMC MUHAMMADIYAH HOSPITAL YOGYAKARTA - Suryanto Suryanto; Adang Muhammad Gugun (Publikasi Indonesia, 2023)
COVID-19 is a global health problem today. Prevention is the best effort, including vaccination. The earliest evidence of the effectiveness of vaccination was marked by an increase in antibody levels. Research is needed to prove the effectiveness of vaccination by measuring levels of SARS-CoV-2 S-RBD antibodies and comparing them with individuals infected with COVID-19. This study aims to determine and prove differences in the levels of SARS-CoV-2 S-RBD antibodies in individuals with a history of COVID-19 vaccination in subjects who have been infected and who have not been infected with COVID-19. The type of research to be conducted is an analytic observational study with a cross sectional design. The variables studied were the levels of SARS-CoV-2 S-RBD antibodies in individuals who received the COVID-19 vaccination. Subjects consist of groups who have experienced infection and who have never been infected with COVID-19. The subjects used in this study were UMY employees who did general post-vaccination check-ups. The sampling technique used purposive sampling method with the inclusion criteria: (i) employees who are actively working (ii) Age 20-56 years (iii) There is a history of infection evidenced by PCR examination evidence (iv) getting vaccinated for more than 2 weeks. Exclusion criteria for employees who have a history of immune or autoimmune deficiency. This research was conducted at AMC Muhammadiyah Hospital. Examination of antibody levels of S-RBD SARS-CoV-2 was carried out using the Elisa method. Data analysis used descriptive method. The research subjects were 90, consisting of 45 subjects who had been exposed and 45 subjects who were not exposed to COVID-19. Subjects exposed to COVID-19 consisted of 25 men and 15 women, while subjects who were not exposed to COVID-19 consisted of 19 men and 26 women. The research subjects were 23 to 64 years old. From the results of the examination of S-RBD SARS-CoV-2 antibody levels, the results showed that the exposed group had a minimum level of 45.16 AU/mL while the maximum level was more than 1,000 AU/mL. In the unexposed group, 12 subjects had levels <3 AU/mL, while the rest had a minimum level of 3.01 AU/mL and a maximum level of 39.6 AU/mL. From this study, it can be concluded that there are differences in the levels of SARS-CoV-2 S-RBD antibodies which are higher in individuals who have been exposed to COVID-19 than individuals who have not been exposed. There are subjects who have not responded to the COVID-19 vaccination.